Discovering genetic interactions bridging pathways in genome-wide association studies - Gang Fang (Nature Portfolio, 2019)
Genetic interactions may contribute to phenotypic traits but are challenging to decipher. Here, the authors develop BridGE, a computational approach for identifying pathways connected by genetic interactions from GWAS data.